Electrochemical noise and impedance study of aluminium in weakly acid chloride solution - Gouveia-Caridade, Carla (2004)
The electrochemical noise (EN) characteristics of pure aluminium in unbuffered potassium chloride solution and with acetic acid/sodium acetate buffer at pH 5.4 and 4.3 have been analysed to throw light on the influence of pH and of the presence of buffer at the aluminium surface on chloride ion-induced corrosion. Comparison has been made with results obtained by electrochemical impedance spectroscopy (EIS) and quantitative deductions made concerning the values of the noise resistance and the magnitude of the electrochemical impedance. Deviations between results obtained by the two experimental techniques are discussed.